The Characteristics of Customer Satisfaction and Subscription Service Usage - Ushio Dazai (Maketingu Janaru, 2022)
This paper is an exploratory study of the characteristics of customer satisfaction with subscription services. In the subscription market, there is a phenomenon where people continue to sign up for subscriptions despite low usage. In this paper, the author explored the relationship between service usage and customer satisfaction based on the data from Oricon’s customer satisfaction survey. The findings showed that there are thresholds at which satisfaction fluctuates with habitual use, i.e., daily and weekly, and that satisfaction is greatly affected when it falls below a specific line, e.g. once a week. The findings also showed that there is a threshold for ideal service usage depending on the service type, that long-term continuity does not strongly affect satisfaction, and that unit price is not related to satisfaction.